E-070 Curative treatment for low grade arteriovenous malformations. (22nd July 2019) - Wang, A; Connolly, E; Solomon, R; Lavine, S; Meyers, P
Abstract : Introduction: Low grade, Spetzler Martin (SM) grade I and II arteriovenous malformations (AVM) are often considered safe for surgical resection or radiosurgery. The use of preoperative arteriography with endovascular embolization to reduce surgical risk in these AVMs remains controversial. The authors assessed the safety of combined treatment of SM I and II AVMs with preoperative embolization followed by curative treatment with surgical resection or radiosurgery. Long term functional outcomes were also studied. Methods: Under IRB-approved protocol, retrospective analysis was carried out on all patients with ruptured and unruptured SM I and II AVMs from 2002 to 2017 using a quality assurance database. Details of the endovascular procedures including arterial supply to the AVM, number of branches embolized, embolic agent(s) used, and complications were studied. Baseline clinical and imaging characteristics were compared, and functional status using the modified Rankin Scale (mRS) before and after endovascular and microsurgical/radiosurgery treatments were compared. Results: 258 SM I (36%) and II (64%) AVMs were identified (mean age 38.3 years). 48% of patients presented with hemorrhage, 21% with seizure, 16% with headache, 10% asymptomatic and 5% with a clinical deficit. 90 patients (68%) in the unruptured group and 74 patients (59%) in the ruptured group underwent presurgical embolization (p = 0.0013). The mean number of arteries supplying the AVM was 1.44 and 1.41 in the unruptured and ruptured groups respectively. The mean number of arteries embolized was 2.51 in the unruptured group compared to 1.8 in the ruptured group (p = 0.003). nBCA and Onyx were the two most commonly used embolic agents. Pre-embolization and post-embolization mRS are shown in tables 1 and 2. Four complications were seen in 164 embolization procedures including two peri/post procedural hemorrhages, one dissection, and one infarct. All patients undergoing microsurgical resection had a complete cure on post-operative angiography. Immediate postoperative mRS and long term follow up mRS (mean of 55 months) was determined after curative treatment. Good long term outcomes (mRS ≤ 2) was seen in 95% of unruptured AVM patients and 92% of ruptured AVM patients postoperatively. Transient and permanent neurological deficits were seen in 5% and 1% of patients after curative treatment. Conclusions: Multimodal therapy of low grade AVMs can be performed with low morbidity and high cure rates in high volume centers. By comparison with other published studies, our outcomes suggest that pre-operative embolization is a safe adjunct to definitive curative treatment. Disclosures: A. Wang: None. E. Connolly: None. R. Solomon: None. S. Lavine: None. P. Meyers: None.